PERBAIKAN BIOPORI OLEH CACING TANAH (Pontoscolex corethrurus). APAKAH PERBAIKAN POROSITAS TANAH AKAN MENINGKATKAN PENCUCIAN NITROGEN ? - Farah Amirat; Kurniatun Hairiah; Syahrul Kurniawan (Jurnal Tanah dan Sumberdaya Lahan, 2014)
The addition of organic fertilizer into soil increased earthworm growth and its activity and, not only for decomposer group but also for soil digger group (ecosystem engineer).Pontoscolex corethrurus is one of ecosystem engineer group create many channel in soil, so that increased soil porosity and infiltration in soil The objective of this research was to study on N leaching in various biopores condition which formed by earthworm`s activity. Various level of soil porosity and nitrate consentration at controlled condition was obtained from application of  mixture of 3 types of litter (coffee, Gliricidia and durian), N-urea fertilizer and soil digger earthworm (Pontoscolex corethrurus) into soil.  The treatments tested were (1) KO : Control 1 (without worm, N-Organik and N-Anorganik); (2) KCC : Control 2 (added earthworm, without N-Organic and N-inorganic); (3) UREA : (added earthworm + N-inorganic, without N-Organik); (4) KGD : (added earthworm and N-Organic, without N-inorganic); (5) KGDU : (added earthworm + N-inorganic + N-Organic). Each treatment was repeated four times. The biopores formed by earthworm was measured  from the length of soil channel  at 1st, 2nd, 4th, 6th and 8th weeks after treatments (WAP). Measurement on earthworm`s growth was conducted with measuring earthworm`s length, diameter, biomass and casting by the end of treatment (8 WAP). Analysis of nitrate in leachete was done at 2nd, 4th, 6th and 8th  WAP. Result of this research showed that application of N-anorganic only led to more active earthworm rather (83 %) than application of N-organic resulting longer vertical channel formed by earthworm.  However, the increasing the length of vertical channel was not followed by increasing of water percolation. Porosity was related to nitrat leached concentration (R2 = 0.36). Total of leaching was not only influenced by porosity but also by another factor like NO3- -available (influence by N source input). Application of N-anorganic increased concentration of leached NO3- (42 %) than application of N-organic (181 mg L-1 concentration of leached NO3-). No significant (p>0.05) correlation between soil porosity and earthworm`s biomass was found.